Female-based urban poverty in parts of Sehore city, India - Siddiqui, Farheen; Parveen, Shahnaz (Quaestiones Geographicae, 2024)
Female-based urban poverty has been a widely researched topic fitting into the pursuit of gender equality since the Beijing 1995 Conference for Women. However, the criteria for measuring female-based urban poverty assume a direct role in reducing various urban poverty manifestations amongst females. Nevertheless, standard domains such as economic and educational statuses show some noticeable characteristics in smaller townships located in the low-urbanised states of India. The city under concern—Sehore Municipal Council (M.C. hereafter)—furnishes an example of an emerging urban area in a low-urbanised state of Madhya Pradesh (27.6% of the urban population compared to the national average of 31.16%) where domain-wise spatial manifestations of female-based urban poverty are noticeable. In addition to the financial aspect of urban poverty, the study attempts to identify local area determinants related to the socio-economic and the cultural environment of Sehore M.C., using standard variables and indicators for the spatial manifestation of female-based urban poverty through a GIS-based multi-criteria decision-making technique of the analytical hierarchy process (AHP). Female-based urban poverty in Sehore M.C., lying within the urban sphere of influence of two metro cities of Bhopal and Indore, is analysed across six domains of economic, educational, social, health, lack of decision-making and time poverty, for 17 selected localities across four wards. Out of the six selected domains, the economic poverty domain turns out to be the strongest, while time poverty is the least dominant. The present model of female-based urban poverty may apply to similar newly urbanising areas falling within the ambit of metro cities in India.